Comedy and cultural critique in American film - Bishop, Ryan, 1959- (Edinburgh University Press, 2013)
This book uses large scale social and cultural trends and major world events to analyse the American comedy film. This is a historical and conceptual study discussing the comedy narrative, comic traditions, and role of visual culture. Grounded in the theoretical writing of Jean Baudrillard, Paul Virilio, Friedrich Kittler and Jacques Derrida, Bishop brings a new perspective to comedy in film suggesting that it is central to staging cultural criticism. He discusses themes such as repetition, automation, material systems of information media, the level of address in a communicative act, and the shifting role of the image. Key features Close analysis of two films to illustrate key points in each chapter Relevant both to film and cultural studies Chronological treatment